2010
DOI: 10.1111/j.1365-2966.2010.17827.x
|View full text |Cite
|
Sign up to set email alerts
|

Cooling rates of neutron stars and the young neutron star in the Cassiopeia A supernova remnant

Abstract: We explore the thermal state of the neutron star in the Cassiopeia A supernova remnant using the recent result of Ho & Heinke that the thermal radiation of this star is well described by a carbon atmosphere model and the emission comes from the entire stellar surface. Starting from neutron star cooling theory, we formulate a robust method to extract neutrino cooling rates of thermally relaxed stars at the neutrino cooling stage from observations of thermal surface radiation. We show how to compare these rates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
166
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(178 citation statements)
references
References 55 publications
12
166
0
Order By: Relevance
“…Testing different models of , one can limit those which are reasonably consistent with observations. All necessary formulae and caveats could be found in [17], Section 4.…”
Section: Vela's Neutrino Cooling Ratementioning
confidence: 99%
See 2 more Smart Citations
“…Testing different models of , one can limit those which are reasonably consistent with observations. All necessary formulae and caveats could be found in [17], Section 4.…”
Section: Vela's Neutrino Cooling Ratementioning
confidence: 99%
“…We will employ the method similar to that discussed in [17,20,34] and in references therein. It is well described in the literature; we just outline the main points.…”
Section: Vela's Neutrino Cooling Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Gabler et al [53] found that for B 5 × 10 13 G torsional crust modes would be resonantly damped by coupling to the Alfvén continuum, with damping timescales ∼ 0.2 s. Their study did not, however, include the effects of proton pairing in the core nor did it include a re-alistic model of the neutron star crust. Observations of cooling of the young neutron star in the Cas A supernova remnant [54,55] suggest that the proton 1 S 0 pairing gap is large [56,57], so that the protons are in a superconducting state throughout the core. The crust-core coupling depends on the magnetic field configuration and the magnetic field strength near the crust-core interface [20], neither of which are well understood.…”
Section: Discussionmentioning
confidence: 99%
“…This introduces many subtleties into their cooling processes, which are not yet fully understood even in the Standard Model (see e.g. [50][51][52][53][54][55][56][57][58][59]). However, neutron stars are such powerful "φ-factories" in dmDM that we can still set very strong constraints despite these uncertainties.…”
Section: Neutron Star Coolingmentioning
confidence: 99%